Displacement of hydrocarbon liquids by water using the models of zonally heterogeneous deformable formations - Marat Ya. Khabibullin; Rustem I. Suleymanov; Razifa R. Stepanova; Alina Az. Gizzatullina; Arsen M. Khabibullin (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The need to predict the main indicators of the development of a gas condensate deposit represented by elastic zonal heterogeneous reservoirs. In this case, the real PVT properties of a two-phase hydrocarbon system and the rheology of reservoir rocks are taken into account. Aim. Based on the study of the causes of high residual gas saturation and oil saturation of hydrocarbon deposits, it is necessary to solve the problem of displacing hydrocarbon liquids with water injected into the reservoir in zonal heterogeneous reservoirs. In this case, a circular reservoir developed by a central well is represented as consisting of two zones with different reservoir-capacity and rheological properties. Objects. The processes of hydrocarbon system filtration to the central well during displacement by water in a zonally heterogeneous formation. The current position of the water front has a radius r_v. The flooding contour has a radius R_k. It is known that the motion of two-phase hydrocarbon systems in deformable reservoirs is represented by complex nonlinear partial differential equations. An analytical solution of such equations is possible only with the use of special approaches. In this paper, the averaging method and the Khristianovich function will be used to linearize the equations. To predict the well flow rate, an algorithm it is necessary to determine the noted reservoir parameters at any time. For this purpose, we will use the material balance equations for the gas and liquid phases of the hydrocarbon system and the volume of water penetrating into the reservoir. Methods. Solution of the equation of unsteady water filtration taking into account boundary and boundary conditions. Results and conclusions. The results are obtained for forecasting the development of the main indicators of displacement of hydrocarbon liquids to the well, when near the well (in the inner zone) and in the remote part of the deposit (i. e. in the outer zone) the formation has different reservoir-capacity and rheological characteristics. The above approach allows determining the main indicators of a gas condensate deposit development under various technological modes, taking into account the difference in permeability and the nature of deformations of the bottomhole zone and in the remote part of the reservoir. The obtained solution allows forecasting the main indicators of the development of a gas condensate deposit represented by elastic zonal-heterogeneous collectors. The proposed algorithm allows simulating almost any technological mode of injection and well. Thus, it is possible to reproduce the mode of a given water injection rate and a given pressure on the flooding contour.